PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP CORPORATE IMAGE PT DAN LIRIS - Tri Wuryan Ningrum; Sudharto Prawata Hadi (Universitas Diponegoro, 2020)
A rapid business growth provides many impacts for the community and the environment around the company. The impacts that appear are positive and negative impacts. For this reason, the company is required to carry out a responsibility for negative impacts arising from business activities carried out. This form of responsibility is commonly known as CSR (Corporate Social Responsibility) where CSR is carried out in order to foster good and harmonious relations with the community so that it can provide opportunities for corporate sustainability. Corporate sustainability can be seen from various aspects, one of which is the image attached to the company and CSR is able to provide a positive image for a company if CSR is carried out in accordance with what is needed by the community and the environment around the company for the impact of company activities.This study aims to identify the effect of CSR on corporate image in PT Dan Liris. The type of research used is descriptive analytical with qualitative approaches. Data collection techniques used consist of interview through informants, observations, and literature studies.